Effect of Organizational Culture and Competence on Employee Performance at PT Banjar Sari Pribumi Lahat - Putri Febri Yanti; Wiwin Agustian (Budapest International Research and Critics University, 2022)
Human resources are the main assets that play a role in utilizing all existing economic resources in the organization. The problem with organizational culture is that there are still employees of PT Banjarsari Pribumi Lahat who are less responsible for the tasks assigned to them, such as ignoring tasks or procrastinating work when the employee is given the task of repairing damaged mining equipment. The selection of quantitative methods with a descriptive approach is based on research that wants to know how much influence competence and organizational culture have on the performance of PT Banjarsari Pribumi Lahat employees. The importance of the company to determine the influence of Competence and Organizational Culture in influencing employee performance. The purpose of the study was to determine the effect of competence and organizational culture on the performance of PT BanjarSari Pribumi Lahat employees. Also, to determine the effect of competence on the performance of employees of PT Banjarsari Indigenous Lahat. In addition, through this research, it is hoped that researchers can contribute and provide additional literature on the Effect of Competence and Work Culture on Performance.